Pancasila as an Industrial Development Paradigm - Moh. Gufron Eramansyah; Safitri; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
This paper aims to find out the concept of Pancasila in the 4.0 industrial revolution by examining Pancasila as a development paradigm. Development includes economic development, education and science and technology. The Industrial Revolution is to become a vision in life, especially focusing on improving the economy, education is designed how to print human resources that can be competitive in the industrial sector. The problem is that the development orientation is more focused in dealing with industrial developments causing the goal in the formation of the nation's personality to be reduced. This was followed by a weakening of the nation's character.Development will not be great if it is not based on the values embodied in the nation's morals, so a development reorientation is needed that refers to the Pancasila State philosophy, because basically Pancasila is a paradigm in development. Pancasila plays a role in providing several ethical principles for economic development, education and science and technology.